2009
DOI: 10.1016/j.cancergencyto.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular centrosome number is correlated with the copy number of chromosomes in bladder cancer

Abstract: Centrosome amplification, which may accelerate tumor progression through chromosomal instability, is frequently observed in human malignancies. However, the intercellular relation between the number of centrosomes and chromosomes is poorly understood. Therefore, the relationship between centrosomes and chromosomal copy number in the same cells was investigated in bladder cancer. Centrosomes were evaluated by immunohistochemistry using anti-γ-tubulin antibody in 8 bladder cancer 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Pihan et al (23) observed that centrosomes were structurally and numerically abnormal in the majority of patients with PCa. Furthermore, bladder cancer samples frequently contain a number of centrosomes that are significantly increased as a result of cytokinesis failure (24). CIT is specifically required during the late stages of cytokinesis for the organization and function of the midbody (7,25).…”
Section: Discussionmentioning
confidence: 99%
“…Pihan et al (23) observed that centrosomes were structurally and numerically abnormal in the majority of patients with PCa. Furthermore, bladder cancer samples frequently contain a number of centrosomes that are significantly increased as a result of cytokinesis failure (24). CIT is specifically required during the late stages of cytokinesis for the organization and function of the midbody (7,25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly this is correlated with an increase in chromosome numbers [48]. Centrosome abnormalities have been detected also in malignant biliary tract diseases.…”
Section: Bladder Cancermentioning
confidence: 93%
“…Breast and prostate cancer [45][46][47] Bladder cancer and Malignant biliary tract disease [48,49] Pancreatic cancer [50] Head and neck sguamous cell carcinoma Oral squamous carcinomas [51][52][53] Neuroectodermals tumours [54] these were found centrosome hyperamplification. Since the percentage is so high, it is implied that this could be used as a marker for HNSCC [51].…”
Section: Abnormalities In Centrosomes In Various Cancersmentioning
confidence: 99%
“…Forced overexpression of Aurora-A in urothelial cells induced CA, chromosome missegregation and aneuploidy 77. Bladder cancer cell lines harbouring Aurora-A and p53 overexpression display supernumerary centrosomes with an even number of chromosome copy number 78. In clinical studies, CA in bladder TCC specimens strongly correlates with concomitant occurrence of cyclin E overexpression and p53 inactivation 76, as well as cyclin D1 gene amplification 75.…”
Section: Centrosome Amplification In Solid Tumoursmentioning
confidence: 95%